IMPELEMENTASI ALGORITMA KRIPTOGRAFI KLASIK CAESAR UNTUK RANCANG BANGUN APLIKASI E-VOTING BERBASIS WEB (STUDI KASUS : SMAN 10 TANGERANG) - Nurul Chafid; Herlina Soffiana (Teknik Informatika Fakultas Ilmu Komputer, 2022)
Elections or we are familiar with the term voting are not only carried out in the election of the legislative council of political parties in a country, the election is also carried out in a school and university organization in the election of candidates for the chairman of the organization or student president. The voting system is always carried out by voting if political opponents or opponents of potential leaders experience the same vote. Voting is an activity carried out to choose a candidate for a predetermined election. In today's modern era, a lot of work is done automatically, including voting, which was previously done manually. Voting that is done manually is done by voting on paper, and the results are calculated on each paper which makes the calculation process take longer. Created a system that can facilitate the voting process. E-Voting is a candidate selection system and the most votes are made and processed in a digital system. System In this voting process there is a process for nominating candidates, selecting candidates, and voting results. With the existence of e-voting to conduct candidate selection with clear and not manipulated data. The data security process is carried out by encrypting data from an existing database using Caesar's Classical Cryptography Algorithm.